Prince Caspian the return to Narnia - Lewis, C. S. (Clive Staples) 1898-1963.; Baynes, Pauline ([New York] HarperTrophy, 1979)
Four children help Prince Caspian and his army of Talking Beasts to free Narnia from evil.
Keywords: Fantasy -- Juvenile